ANALISIS KONSEPTUAL SIKAP DAN KESADARAN DALAM MEMBENTUK PROFESIONALITAS PENDIDIK - Sri Wahyuni; Ainun Nurul Aqidah; St. Ananda Tiara Hanasir (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This article aims to conceptually analyze the role of attitudes and awareness in shaping educator professionalism. This research uses a qualitative approach involving a review of various relevant scientific sources. Content analysis was used as a data analysis technique to identify, categorize, and synthesize relevant ideas. The results indicate that educator professionalism is not solely determined by technical skills but is also influenced by internal factors, such as professional perspective and reflective awareness. Professional awareness serves as an internal foundation that leads to meaningful pedagogical actions, while professional perspective represents internalized values. Consistent professional behavior is shaped by both through a dynamic and mutually reinforcing relationship. According to the findings of this study, educator professional development must be carried out comprehensively by combining skills, attitudes, and awareness through a reflective and ongoing approach.